Speed and need: twin development challenges in rapid response for a SARS-CoV-2 antibody cocktail. (August 2022) - Lehman, Aimee; Muñiz, Virginia A.; Chaney, Ryan; Pimentel, Joseph; Mattila, John; Lawrence, Shawn
Abstract : Neutralizing antibodies are one available tool for the treatment of infectious diseases. Speed in developing monoclonal antibody treatments is an understood requirement for emerging infectious diseases, and need for COVID-19 treatments during the worldwide pandemic has provided additional urgency. Process development (at Regeneron) and technology transfer (within Regeneron and to Genentech) of casirivimab and imdevimab (REGEN-COV™ or Ronapreve™) manufacturing processes have addressed speed and need with selected purification and cell culture examples provided, respectively, for these two development challenges. This was achieved through three key pillars: (1) Regeneron's proprietary Velocisuite® technologies, (2) deep monoclonal antibody process and manufacturing knowledge at both companies, and (3) Regeneron's and Genentech's commitment to deliver therapeutics to patients in need. Combined with business processes and risk management, these pillars rapidly allowed casirivimab and imdevimab to move to clinical manufacturing and to production at Genentech in a first-time process transfer under compressed timelines between the companies. Graphical Abstract: ga1 Highlights: Speed and need of the COVID-19 treatment started with Regeneron platform technologies. Regeneron and Genentech used considerable monoclonal antibody development experience . Specific examples of purification activities emphasize timeline acceleration. Specific examples of cell culture activities emphasize scale-up to address the need.